Tracing Environmental Sustainability Discourses: An Australia-Asia Seafood Case Study - Cullen-knox, Coco; Fleming, Aysha; Lester, Libby; Ogier, Emily (Frontiers in Marine Science, 2020)
The seafood market is highly globalised with a growing demand for seafood and fish products worldwide. The capacity of wild fisheries is limited and therefore aquaculture is fast becoming the most stable source of seafood to meet increasing demand. Subsequently, the perceived environmental risk of fin-fish aquaculture has been the focus of substantial environmental campaigning, media and public scrutiny around the world. This paper places localised tensions regarding the environmental impacts of salmon aquaculture within transnational environmental sustainability debates concerning seafood production and vice-versa, with a focus on the Australia-Asia region. The results contribute to understanding the interpretation and communication of environmental sustainability of seafood through international supply chains and to audiences at different spatial scales. The paper draws particularly on the case of salmon aquaculture in Tasmania, Australia’s southern island state. It highlights mechanisms, such as certification, for which information flows transnationally regarding the environmental sustainability of seafood production, the resultant transnational and local public sphere and the implications for local discourse, market access, governance and certification of seafood production.